Motivation to visit the Giant Panda Conservation Centre in Zoo Negara, Malaysia - Ramli, Fatin; Ramachandran, Sridar (Taylor's University, 2016)
This paper aims to identify factors that affect motivations to visit the Giant Panda Conservation Centre (GPCC). The significant motivational dimension among visitors and how these motivational factors and socio-demographic factors influence the time spent at the GPCC in Zoo Negara, Malaysia are explored. Face-to-face interviews were conducted among visitors to the GPCC. A factor structure which consisted of 15 factors within several motivational dimensions was derived. Results demonstrated that all the factors present high loading values to explain overall motivation. Findings showed that among the motivational dimensions, altruism appeared as the strongest motive followed by intrinsic social motive while self-interest scored the lowest. Findings from multivariate analysis showed that intrinsic social motive and edu-tourism, as well as the socio-demographic variables of age, travel companion and ethnicity, were significantly related to time spent. Age emerged as the most significant independent variable influencing the time spent by visitors. This explorative study of visitors to the GPCC contributes insight into the motives of people visiting the GPCC, how motives are related to the time spent at the GPCC, and how sociodemographic factors are related to time spent. Zoo Negara's management can utilise these findings to prepare future marketing, product development and extension strategies for the GPCC as an attractive destination. of